2018
DOI: 10.1159/000494544
|View full text |Cite
|
Sign up to set email alerts
|

Functional Polymorphisms of CTLA4 Associated with Aggressive Periodontitis in the Chinese Han Population

Abstract: Background/Aims: CTLA4 has been identified functioning as a protein receptor which functions as an immune checkpoint, downregulating the immune system. Susceptibility to aggressive periodontitis (AgP) is influenced by gene polymorphisms related to the immune response. In this study, we focused on SNPs in the 3’-UTR of CTLA4 among Chinese AgP patients, and investigated any further relationships between the SNPs and miRNAs. Methods: This case–control study included 120 AgP patients and 150 healthy controls. Geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 22 publications
0
12
0
1
Order By: Relevance
“…124 A study evaluated neuropeptide single nucleotide polymorphism (Table 4). 126 Because of its much lower prevalence, it is even more challenging to conduct genome-wide association studies with enough power to detect genetic associations for aggressive periodontitis. The number of cases and controls to obtain a significant association has to very high as the P-value to be considered significant in a genome-wide association studies analysis must be very low (<5 × 10 Abbreviations: AgP, aggressive periodontitis; CI, confidence interval; CP, chronic periodontitis; CXCL5, chemokine (C-X-C motif) ligand 5; DEFA1A3, defensin alpha 1-3; GAP, generalized aggressive periodontitis; GLT6D1, glycosyltransferase 6 domain containing 1; GWAS, genome-wide association studies; LAP, localized aggressive periodontitis; MTND1P5, mitochondrially encoded NADH:ubiquinone oxidoreductase core subunit 1 pseudogene 5; PF4, platelet factor 4; PPBP, pro-platelet basic protein; OR, odds ratio; SHISA9, shisa family member 9; SIGLEC5, sialic acid binding Ig-like lectin 5; SNP, single nucleotide polymorphism; UGT2A1, UDP glucuronosyltransferase family 2 member A1 complex locus.…”
Section: Vitamin Dmentioning
confidence: 99%
“…124 A study evaluated neuropeptide single nucleotide polymorphism (Table 4). 126 Because of its much lower prevalence, it is even more challenging to conduct genome-wide association studies with enough power to detect genetic associations for aggressive periodontitis. The number of cases and controls to obtain a significant association has to very high as the P-value to be considered significant in a genome-wide association studies analysis must be very low (<5 × 10 Abbreviations: AgP, aggressive periodontitis; CI, confidence interval; CP, chronic periodontitis; CXCL5, chemokine (C-X-C motif) ligand 5; DEFA1A3, defensin alpha 1-3; GAP, generalized aggressive periodontitis; GLT6D1, glycosyltransferase 6 domain containing 1; GWAS, genome-wide association studies; LAP, localized aggressive periodontitis; MTND1P5, mitochondrially encoded NADH:ubiquinone oxidoreductase core subunit 1 pseudogene 5; PF4, platelet factor 4; PPBP, pro-platelet basic protein; OR, odds ratio; SHISA9, shisa family member 9; SIGLEC5, sialic acid binding Ig-like lectin 5; SNP, single nucleotide polymorphism; UGT2A1, UDP glucuronosyltransferase family 2 member A1 complex locus.…”
Section: Vitamin Dmentioning
confidence: 99%
“…Antibodies that block checkpoints, also bring adverse effects such as the breakdown of self-tolerance, which highlights its role in the physiological modulation of immune responses and therefore has been used as a target of agonist agents to restore tolerance in the context of autoimmunity ( 122 ). In periodontitis, an increase in the expression of CTLA4 on CD4 + T-cells has been found related to the presence of periodontitis and, more recently, the study of these IR has specifically focused on the context of the relationship of possible polymorphisms of the gene that encodes it with susceptibility to specific forms of periodontitis in different populations ( 123 125 ) ( Figure 1E ).…”
Section: Introductionmentioning
confidence: 99%
“…64 Therefore Tregs expressing inhibitory molecule CTLA-4 are supposed to attenuate inflammatory responses against periodontopathogens or antigens. 32,42 Despite the available GWAS data did not provide genetic information of each cohort hence prevented further meta-analysis in relation to SNPs of interests detectable in the current investigation, a Supporting Information Table S5 is prepared to summarize the stated P concerning the nine SNPs with adjusted allelic P < 0.1 reported in the present study. It is noteworthy that Shungin et al 13 reported none of the nine SNPs, including rs5742909 or rs1800796, was associated with periodontitis.…”
Section: Discussionmentioning
confidence: 99%
“…Within periodontal tissue, CTLA‐4 can suppress proliferation of T‐cells in response to periodontopathogens 64 . Therefore Tregs expressing inhibitory molecule CTLA‐4 are supposed to attenuate inflammatory responses against periodontopathogens or antigens 32,42 …”
Section: Discussionmentioning
confidence: 99%